Prevalence of Malaria among Malnutrition Under-five Children Admitted in Nutrition Centers in Northern Bahr el Ghazal State, South Sudan - , Olusola Oladeji, Dick Damas Chamla, Chandrakala Jaiswal, Joy Kenyi, Joseph Senesie, Anne Laevens, Penelope Campbell, Chantal Umutoni (Archives of Current Research International, 2018)
Aims: The ongoing conflict in South Sudan has led to the disruption of health care services with a high burden of infectious diseases, a widespread food insecurity and elevated child malnutrition with malaria being a major cause of co-morbidity among malnourished children. This study assessed the prevalence of malaria among malnourished children and assessed the relationship between malaria and malnutrition among malnourished children in an area with a high degree of malaria transmission. Study Design: This was a retrospective chart review of children 6 month-5years admitted at the nutrition centers Place and Duration of Study: 49 nutrition centers in Northern Bahr el Ghazal state of South Sudan between January 2017 and December 2017. Methodology: A retrospective chart review of sociodemographic, anthropometric and malaria testing data extracted from the treatment cards and registers of malnourished children admitted at the nutrition centre analysed using descriptive and inferential statistic by means of SPSS version 21. Chi square test was used to conduct bivariate analysis to assess the factors associated with malaria at a significant level of 5%. Results: Among the 2124 malnourished children admitted into the nutrition program, 873 (41.1%) had severe acute malnutrition (SAM) and 1251(58.9%) had moderate acute malnutrition. The prevalence of malaria was higher among children with moderate acute malnutrition with 43.2% being positive on testing to malaria compared to 36.4% among children with severe acute malnutrition and bivariate analysis done showed a significant association between malaria and nutritional status (p=0.001). Conclusion: Study highlighted the need for routine screening and testing for malaria to be included in the management protocols for all children admitted into both Outpatient Therapeutic Program and Supplementary Feeding Program in all Nutrition treatment centers to reduce the impact of malaria being a major co-morbidity in the treatment outcome of the children.